IMPORT SUBSTITUTION INDUSTRIALIZATION IN POWER ENGINEERING INDUSTRY - D. Arifulova; E. Reshetova (Вестник университета)
The article examines the dependence of power engineering industry in Russia on imported equipment in general, as well as in the field of gas turbine technologies. The analysis of the equipment of foreign production of the electric power industry of Russia operating at the objects is given, the countries-producers of the installed and currently used foreign equipment in the electric power industry are identified. The role of the Eurasian Economic Union in the framework of import substitution programs has been singled out. Also the international experience of solving problems on reducing dependence on foreign companies is analyzed.